All about ablaut: a typology of ablaut reduplicative structures - Wivell Grace; Miatto Veronica; Karakaş Ayla; Kostyszyn Kalina; Repetti Lori (Linguistic Typology)
In this typological study, we identify 31 languages that have reduplication with a changed vowel, as in English tick-tock, referred to as ablaut reduplication. Cross-linguistically, this type of reduplication typically manifests as total reduplication with a changed vowel whose quality may or may not be fixed, and when it is not fixed the vowel differs maximally from the corresponding vowel in the base. The order of the copy relative to the base can be fixed or variable, and when it is variable the order enforces a language-specific vowel contour across the two components, such as a low vowel in the first constituent and a high vowel in the second, regardless of which constituent is the base. Furthermore, all cases of ablaut have strikingly similar semantics (playfulness, onomatopoeia, movement, etc.). We review previous treatments of the topic and outline the necessary components of a unified analysis that accommodates the typological patterns.